A field-based framework for evaluating sustainable fishing gear in small-scale Plesionika edwardsii fisheries - Monfardini, Eleonora; Ciaralli, Laura; Catalano, Barbara; Franceschini, Gianluca; Antonini, Camilla; Trabucco, Benedetta; Di Lorenzo, Bianca; Finoia, Maria Grazia; Nonnis, Ornella (Frontiers in Marine Science, 2025)
IntroductionPlastic pollution at sea is a critical global issue, but despite legislative requirements, scant information is available for the ongoing assessment of this threat. Abandoned, lost, or otherwise discarded fishing gear (ALDFG) significantly contributes to marine litter, ghost fishing, and ecosystem degradation.MethodsA multidisciplinary research effort, carried out in collaboration with small-scale fishers, introduced a new methodological approach implementing sustainable and biodegradable fishing gear. This approach combined experimental field trials with performance monitoring to test pot nets lined with biodegradable and compostable material prototypes, used in artisanal fisheries targeting Plesionika edwardsii.ResultsAccording to our results, these alternative materials deliver artisanal performance comparable to that of traditional plastics, including fishing efficacy, while reducing environmental impact.Discussion/ConclusionEarly-stage trials indicate that biodegradable pots, while requiring further refinement for effective use in fishing, represent a viable option for reducing ghost fishing and plastic pollution, supporting biodiversity conservation. This work demonstrates a replicable framework for testing and validating sustainable fishing gear under real-world conditions, supporting evidence-based decisions in marine resource management.